Analisis Pengaruh Efikasi Diri terhadap keinginan berpindah Kerja dengan Kepuasan Kerja sebagai Variabel Pemediasi - Erni Rohmawati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2018)
This study was aimed to test the influence of self efficacy toward job turnover intention with job satisfaction as intervening variable. The sample was 218 auditor independent in Indonesia. The result of this study showed that self-efficacy positively influence toward job satisfaction and job turnover intention, and job satisfaction negatively influence toward job turnover intention. On the third result contrast with Bandura theory (1997) that suggest people who have strong self efficacy will have positive value toward their jobs. While in this study found that people who have strong self efficacy, they will have high job turnover intention. This study found that auditors who work in auditor company have high interest to look for a better job chance and challenge of their career.